2016
DOI: 10.31018/jans.v8i4.1130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-harvest application of gibberellin and brassinosteroid on fruit growth and quality characteristics of pear (Pyrus pyrifolia (Burm.) Nakai) cv. Gola

Abstract: Quality of fruit crop is an important parameter to decide the acceptability of the product. The present study consists of seventeen year old pear (Pyrus pyrifolia (Burm.) Nakai) trees subjected to seven treatments viz., GA3 (50 ppm,100 ppm), BR (0.5 ppm, 1.0 ppm), and GA3 + BR (50 ppm + 0.5 ppm and 100 ppm + 1 ppm) and water as control, sprayed thrice at 15 days intervals starting from petal fall stage. Each treatment was replicated thrice with one tree served as a treatment unit. The experiment was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Its physiological efficacy is activating the translocation and assimilation of metabolic materials, enhancing photosynthesis activity, and hormonal regulation of plant morphogenesis according to Guo et al (2011) andNisler (2018). These findings of brassinolide treatments agreed with those obtained by (Tadaion et al, 2014) on 'Khalili' grapevine; Roghabadi and Pakkish (2014) on 'Tak Danehe Mashhad' sweet cherry, they all found that brassinolide treatments significantly increased total soluble solids, total sugars, anthocyanin and vitamin C. Thapliyal et al (2016) on pear and Ghosh et al (2022). The application of BR can lead to an increase in sugars in fruits, as BR indirectly increases the content of abscisic acid (ABA), which in turn induces the sugar metabolic pathway.…”
Section: Total Sugars (%)supporting
confidence: 85%
See 2 more Smart Citations
“…Its physiological efficacy is activating the translocation and assimilation of metabolic materials, enhancing photosynthesis activity, and hormonal regulation of plant morphogenesis according to Guo et al (2011) andNisler (2018). These findings of brassinolide treatments agreed with those obtained by (Tadaion et al, 2014) on 'Khalili' grapevine; Roghabadi and Pakkish (2014) on 'Tak Danehe Mashhad' sweet cherry, they all found that brassinolide treatments significantly increased total soluble solids, total sugars, anthocyanin and vitamin C. Thapliyal et al (2016) on pear and Ghosh et al (2022). The application of BR can lead to an increase in sugars in fruits, as BR indirectly increases the content of abscisic acid (ABA), which in turn induces the sugar metabolic pathway.…”
Section: Total Sugars (%)supporting
confidence: 85%
“…'Huangjinmiyou' and 'Hongroumiyou'. ;Thapliyal et al (2016); Aly et al (2021), noticed that the foliar application treatments of brassinolide at 1.5mg/L and 2mg/L treatments significantly increased fruit length, fruit diameter and fruit size. Roghabadi and Pakkish (2014) and EL-Boray et al (2015) found that foliar applications of brassinolide increased fruit firmness at harvest.…”
Section: Fruit Firmness (Lb/inch 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Brassinosteroids are well known to promote photosynthesis efficiency by enhancing regeneration of RuBP and followed by an increase of CO2 fixation in photosynthesis. It also regulates stomatal activity and increases level of CO2 inside the leaves [7]. Application of triacontanol attributed to more efficient utilization of food for reproductive growth, flowering and fruit set, higher photosynthetic efficiency and enhanced source to sink relationship of the plant, increased uptake of nutrients and water, reduced transpiration and respiration, enhanced translocation and accumulation of sugar and other metabolites [5].…”
Section: Resultsmentioning
confidence: 99%
“…The time of application plays a crucial role in deciding the desirable output and the combined application of gibberellin and brassinosteroid either at GA3 (100 ppm)+BR (1 ppm) or GA3 (50 ppm)+BR (0.5 ppm) as pre-harvest spray at 15 days interval starting from the petal fall stage may be recommended for improving the fruit quality of Gola pear in Tarai region [94]. As specified by [45] observed that exogenous BR treatment suppressed ethylene production and delayed fruit ripening, whereas treatment with a BR biosynthesis inhibitor promoted ethylene production and accelerated fruit ripening in hence BR has been suggested as a ripening suppressor.…”
Section: Pearmentioning
confidence: 99%